Floristic and phytogeographic analysis of the Sabanas Miravalles in Costa Rica - Jiménez Vargas, José Esteban (2025)
Background and Aims: The savanna ecosystem in Costa Rica, which covers small areas along the Pacific slope (100-1500 m a.s.l.), and particularly the Sabanas Miravalles, on the western flank of Volcán Miravalles (Cordillera de Guanacaste), remain floristically understudied. The aims of this study are to inventory the vascular flora of Sabanas Miravalles, assess its ecological importance, evaluate spatial heterogeneity's impact on composition, and compare their phytogeographic affinities with other Neotropical savannas. Methods: We identified the vascular flora within 25 plots of 50 × 10 m, classified by life form following Raunkiær, and divided into woody and herbaceous (graminoid and non-graminoid herbs) species. We analyzed the composition and floristic affinity with species accumulation curves, Chao1 index, Relative Importance Value (RIV), Bray-Curtis and Sørensen indices. Key results: A total of 54 families, 161 genera, and 228 species were documented. Fabaceae was the most diverse family, and Polygala and Rhynchospora were the most diverse genera. Non-graminoid herbs and hemicryptophytes were dominant. Miconia sericea, Polygala glochidata, and Trachypogon plumosus were the most abundant in their growth form. Floristic composition exhibited clear elevation-driven shifts, with three main groups identified. Most species exhibited wide Neotropical distributions. The flora of the Sabanas Miravalles showed the greatest similarity to the Venezuelan Llanos, with 70% of species in common. Conclusions: The flora of the Sabanas Miravalles represents 2.1% of Costa Rica's ~10,712 vascular plant species. Although its origin is uncertain, Pleistocene floristic exchanges, volcanic eruptions, and fire have likely shaped its composition. Understanding its origin, phytogeographic affinities, and physical drivers is essential for effective management and conservation.